Evaluation of Time-to-Delivery and Identification of Delay Factors in B2B Internet Services - Pangestu, Prayoga; Nusraningrum, Dewi (International Journal Labs, 2025)
This research addresses the problem of delayed B2B internet service installations at PT Telkom Indonesia Witel Jakarta Barat, which fails to meet the regulatory requirement of 95% on-time completion within a seven-day service-level agreement (SLA ? 7 days) as stipulated in Ministry Regulation No. 15/2013. An evaluation of 3,394 orders in Q1 2024 revealed only 90.20% on-time completion, highlighting the need for process improvement. The objective of this study is to identify bottlenecks, streamline the installation value stream, and enhance SLA compliance through the integration of Value Stream Mapping (VSM) and Kaizen methodologies. Using VSM, the study identified 140 hours of value-added time (VA-time) spread across the site-survey, cable-pulling, and activation stages, with more than half lost due to scheduling delays and material shortages. Kaizen initiatives—including the digitalization of technician scheduling, standardized work-order formats, and regular 5S audits—successfully reduced VA-time to 7 hours, achieving a 95% efficiency rate in the future-state process. Simulation of the improved process demonstrated SLA compliance exceeding 97% and a noticeable reduction in customer complaints. Furthermore, warehouse and fleet 5S audit scores, indicating better orderliness and safety. These findings imply that the combined VSM–Kaizen approach effectively eliminates non-value-adding activities, accelerates service delivery, and ensures regulatory compliance, offering a replicable model for operational improvements in the telecommunications industry.